Pentingnya pengelolaan Dana Sumbangan Pendidikan (DSP) di PAUD Plus Darussalam Bojonegoro - Rachma Nur Afida; Ary Yunita Anggraeni (University of Merdeka Malang, 2020)
This study aims to determine the input and payment system for the Education Contribution Fund (DSP) at PAUD Plus Darussalam. So far, payment management is still done manually, thus slowing down the financial administration process. The system designed makes financial management run effectively and efficiently. This system is designed using Microsoft Excel Macro. The stages of developing this system are expected to facilitate data retrieval, provide complete, fast, accurate information and facilitate access to financial data and information. Keywords: Data, Management, DSP Payment